Inhibitory action of exogenous cardiolipin on the bacterial type i and ii dna topoisomerases in vitro - Yu. L. Mikulovich; G. М. Sorokoumova; А. А. Selishcheva; V. I. Shvets (Тонкие химические технологии, 2012)
The influence of empty liposomes composed of cardiolipin (lipid which is a component of the bacterial cytoplasmic membrane and eukaryotic internal mitochondrial membrane) on Escherichia coli topoisomerase I and DNA gyrase (topoisomerase II) in vitro was investigated. Cardiolipin was found to inhibit the reaction of DNA relaxation catalyzed by topoisomerase I and both reactions catalyzed by DNA gyrase, namely DNA relaxation (in the absence of ATP) and DNA supercoiling (in the presence of ATP). On the basis of the results obtained along with the bactericidal action of cardiolipin on Mycobacterium tuberculosis and Escherichia coli earlier found by us we suppose that topoisomerases could be the targets of cardiolipin.